Structural insights into brassinosteroid export mediated by the Arabidopsis ABC transporter ABCB1 - Wei, Hong; Zhu, Heyuan; Ying, Wei; Janssens, Hilde; Kvasnica, Miroslav; Winne, Johan M; Gao, Yongxiang; Friml, Jiří; Ma, Qian; Tan, Shutang; Liu, Xin; Russinova, Eugenia; et al. (Plant communications, 2025)
Brassinosteroids (BRs) are steroidal phytohormones indispensable for plant growth, development, and responses to environmental stresses. The export of bioactive BRs to the apoplast is essential for BR signaling initiation, which requires binding of a BR molecule to the extracellular domains of the plasma membrane-localized receptor complex. We have previously shown that the Arabidopsis thaliana ATP-binding cassette (ABC) transporter ABCB19 functions as a BR exporter and, together with its close homolog ABCB1, positively regulates BR signaling. Here, we demonstrate that ABCB1 is another BR transporter. The ATP hydrolysis activity of ABCB1 can be stimulated by bioactive BRs, and its transport activity was confirmed in proteoliposomes and protoplasts. Structures of ABCB1 were determined in substrate-unbound (apo), brassinolide (BL)-bound, and ATP plus BL-bound states. In the BL-bound structure, BL is bound to the hydrophobic cavity formed by the transmembrane domain and triggers local conformational changes. Together, our data provide additional insights into ABC transporter-mediated BR export.
Keywords: proteiny huseníčku; Brassinosteroids; steroidy heterocyklické; brassinosteroids; brassinosteroidy; Adenosine Triphosphate; adenosintrifosfát; biologický transport; Arabidopsis Proteins; ABC transportéry; Steroids, Heterocyclic; ABCB1; transport; structure; signaling; Arabidopsis; Biological Transport; ATP-Binding Cassette Transporters